The concept of disability - Amiralian, Maria LT; Pinto, Elizabeth B; Ghirardi, Maria IG; Lichtig, Ida; Masini, Elcie FS; Pasqualin, Luiz (Revista de Saúde Pública, 2000)
One of the major problems in research and health practice related to impairment is the inaccuracy of definitions all over the world, which makes it difficult to exchange information obtained by different authors. In this paper, the concepts of impairment, disability and handicap are discussed based on the publication by the National Secretariat for Rehabilitation of the World Health Organization (Portugal, 1989) and the analysis of recent publications related to this subject. Four categories were established: a) concepts; b) application of concepts; c) questions related to terminology and; d) theoretical models and their implication. Disparities, consistencies and breadth of this literature were also analyzed giving emphasis to the importance of the terminology used to provide general understanding and better communication between experts.